Pengaruh Volume dan Frekuensi Pemberian Air Cucian Beras Terhadap Pertumbuhan Bibit Tanaman Karet (Hevea brasiliensis Muell.) Klon GT 1 - Mira Ariyanti; Cucu Suherman; Santi Rosniawaty; Albert Franscyscus (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2018)
Rubber is one of main commodities of plantation crops that numerously developed in various districts in Indonesia. The role of the plant is strategic in human life in line with the increasing demand of world rubber. The optimum production increament of the rubber plant begins with the selection of a superior clone and the use of quality seeds. Fertilizing as a means of providing soil nutrients to plants should also be taken carefully. One of the fertilization is by the provision of organic fertilizers in the form of washed rice water. This research aims to find out the effect of washed rice water in a different volume and frequency applied as organic fertilizer on the growth of rubber seedling GT1 clone.The experiment wasconductedfrom September 2011 toJanuary2012 atthe Experimental Station of Faculty of Agriculture, Universitas Padjadjaran. The experiment was arranged inRandomized Block Designed, with 9 treatments and 3 replications, thus there are 27 units of the experiment. The treatments were providing 100 ml washed rice water with frequency of 3 days, 100 ml washed rice water with frequency of 5 days, 100 washed ml rice water with frequency of 7 days, 300 ml washed rice water with frequency of 3 days, 300 ml washed rice water with frequency of 5 days, 300 ml washed rice water with frequency of 7 days, 500 ml washed rice water with frequency of 3 days, 500 mL washed rice water with frequency of 5 days, and 500 ml washed rice water with frequency of 7 days. The results of the experiment showed that by providing 500 ml washed rice water with frequency of 3 days gave the best increament for stem height and diameter on rubber seedling GT1 clone.